THE ROLE OF LABORATORY TESTS IN MONITORING INFECTIOUS DISEASES IN CHILDREN - Marufova Shaxzoda Furkatovna; Isomadinova Lola Kamolidinovna; Yulayeva Irina Andreevna (Web of Journals Publishing, 2025)
Infectious diseases are a major concern in pediatric medicine, with the potential to cause significant morbidity and mortality. Timely and accurate diagnosis is essential for effective treatment and prevention of complications. Clinical laboratory tests are invaluable tools in the diagnosis, monitoring, and management of infectious diseases in children. This article reviews key laboratory tests commonly used to diagnose and monitor various pediatric infections, including bacterial, viral, and parasitic infections. Tests such as complete blood count (CBC), C-reactive protein (CRP), procalcitonin (PCT), and microbiological cultures provide important information regarding the nature of the infection, its severity, and the response to treatment.
Keywords: Infectious diseases, pediatrics, laboratory tests, CBC, CRP, procalcitonin, microbiological cultures, bacterial infections, viral infections, parasitic infections.